Globalização das políticas públicas de educação básica no Governo Lula: uma metodologia para a democracia participativa em municípios brasileiros - Silva, Carlos Eduardo Moreira da (2016)
This thesis has the aim of analyzing the challenges and possibilities of collective creation of public policy instruments of basic education in eminently rural towns in Paraná, as also in Santa Catarina states during Lula’s government period in Brazil. This construction includes cultural as well as local political factors as part of a wider globalization process and the definition of the Globally Structure Agenda for the education, which has been oriented and imposed by multilateral agencies and the hegemonic States to be taken over by national States. It commenced with the finding of a confrontation scenery between the hegemonic globalization, which has imposed structural adjustment to the national State in order to ensure better conditions for capital accumulation, and counter-hegemonic globalization characterized by training practices for the consolidation of civic participation in public areas. These forms of globalization coexisted in a contradictory way in the field of educational public policies in Brazil, with implications that should have been better analyzed and verified as they were understood and assumed by subnational governments and school communities. As part of the systematization experience of popular education, this study contributes to the real experiences, theoretical reflection of participatory methodology application of educational planning in school communities. It provides a set of reflections about how the democratic inducer public policy of Lula’s government has been received in the towns focused in this research. In the first hypothesis, subnational governments had full conditions to carry out an educational project, considering the teaching educational legislation and the Education Ministry guidelines, according to what the global agenda for education determines, using the political and administrative decentralization and the transfer of financial resources. In the second hypothesis, it all started with the idea that there were not any conditions for the construction of an educational project due to lack of interest of subnational governments own resources or transferred by the national government. In the third hypothesis, the educational project construction could be achieved taking advantage of the “legal loopholes”, the inducer policy of Lula’s government, and especially the aims and strategies of the Strategic Participatory Educational Planning Methodology (SPEP), which makes use of the “Gramscian strategies of democratic conspiracy” to define collectively a planned action to be continuously monitored and evaluated by the school communities and town hall sectors as well as by the society in general. From this hypothesis, a participatory research approach through the application of technology (SPEP) has been developed, which has produced numerous reflections on Lula’s government inducer educational policy, and has revealed tensions arising from conflicts with the local political culture and the habitual forms of social participation in the towns that were studied. Finally, once analyzed the challenges and possibilities for the public policy collective construction of basic education, it is concluded that it is possible to carry out the collective construction through intensive investigative and formative processes of participatory methodologies that contribute to the empowerment of the social individuals directly involved and committed to striving for the achievement of social quality of the municipal public education